The implementation of a new Malaria Treatment Protocol in Timor-Leste: challenges and constraints - Martins, João Soares (Oxford University Press, 2012)
Background Timor-Leste changed its malaria treatment protocol in 2007, replacing the first-line for falciparum malaria from sulphadoxine-pyrimethamine to artemether-lumefantrine. This study explored the factors affecting the implementation of the revised treatment protocol, with an emphasis on identifying key constraints. Methods A mixed method approach drew on both qualitative and quantitative data. The study included data from District Health Services in seven districts, community health centres in 14 sub-districts, four hospitals, five private clinics, one private pharmacy and the country's autonomous medical store. In-depth interviews with 36 key informants, five group interviews and 15 focus group discussions were conducted. A survey was also undertaken at community health centres and hospitals to assess the availability of a physical copy of the Malaria Treatment Protocol, as well as the availability and utilization of artemether-lumefantrine and sulphadoxine-pyrimethamine. Results Many factors impeded the implementation of the new malaria protocol. These included: inadequate introduction and training around the revised treatment protocol; unclear phasing out of sulphadoxine-pyrimethamine and phasing in of the revised treatment, artemether-lumefantrine, and the rapid diagnostic test (RDT); lack of supervision; lack of adherence to the revised guidelines by foreign health workers; lack of access to the new drug by the private sector; obstacles in the procurement process; and the use of trade names rather than generic drug description. Insufficient understanding of the rapid diagnostic test and the untimely supply of drugs further hampered implementation. Conclusion To effectively implement a revised malaria treatment protocol, barriers should be identified during the policy formulation process and those emerging during implementation should be recognized promptly and addressed.